2019
DOI: 10.1002/phar.2318
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Helicobacter pylori in Special Patient Populations

Abstract: Helicobacter pylori infection can lead to gastritis, gastric and duodenal ulcers, and gastric cancer. Consequently, complete eradication is the goal of therapy. First‐line therapy for H. pylori infection includes clarithromycin triple therapy (clarithromycin, proton pump inhibitor [PPI], and amoxicillin or metronidazole), bismuth quadruple therapy (bismuth salt, PPI, tetracycline, and metronidazole or amoxicillin), or concomitant therapy (clarithromycin, PPI, amoxicillin, and metronidazole). However, many pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 79 publications
(226 reference statements)
1
16
0
Order By: Relevance
“…The treatment of H pylori in patients with penicillin allergy—a relatively frequent scenario—represents a significant challenge, as amoxicillin is one of the most effective antibiotics against this infection, and acquired resistance is rare 6 . Only few studies, including very low number of patients, have evaluated H pylori first‐line eradication treatments in patients with penicillin allergy (summarized in Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of H pylori in patients with penicillin allergy—a relatively frequent scenario—represents a significant challenge, as amoxicillin is one of the most effective antibiotics against this infection, and acquired resistance is rare 6 . Only few studies, including very low number of patients, have evaluated H pylori first‐line eradication treatments in patients with penicillin allergy (summarized in Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…A history of penicillin allergy reported by the patient or general practitioner is common, often based on remote recollection without documentation. Moreover, the term “allergy” may be used by patients to denote any past adverse drug reaction 6,35 . Thus, it has been suggested that formal penicillin allergy testing may be done for the patients with a remote or unlikely history of allergy to determine whether they may be able to tolerate a penicillin or amoxicillin challenge 6,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 14‐day high‐dose dual therapy consisting of a standard or double dose of PPI and a total of 3 g/d amoxicillin was recommended as a salvage regimen for H pylori treatment in the ACG Clinical Guideline 37 . Given the ground of similar efficacy, 38 less pill exposure, lower risk of major drug interactions, and lower potential for AEs, amoxicillin‐based dual therapy may be considered as an alternative therapy in special patients 39 . In our study, a 14‐day dual regimen consisting of 10 mg rabeprazole and 1000 mg amoxicillin 3 times per day achieved a satisfactory eradication rate of 90.9% as the first‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The elderly population is more likely to be resistant to antibiotics because of excessive use in the past ( 91 , 92 ). A multicenter cohort study showed that people aged >40 years were particularly at risk of developing dual drug resistance to levofloxacin and metronidazole ( 93 ).…”
Section: Treatmentmentioning
confidence: 99%